Isolated functional tricuspid regurgitation, how define patient at-risk for event?. (3rd October 2022) - L'official, G; Vely, M; Guerin, A; Chen, E; Dreyfus, J; Sportouch, C; Oger, E; Donal, E
Abstract: Introduction: Functional tricuspid regurgitation (TR) is a turning point in cardiac diseases. Symptoms typically appear late, and the optimal timing for proposing a valve repair remains a challenge. We sought to analyse the characteristics of right heart remodelling in patients with significant functional TR to identify the parameters that could be used in an easily achievable and fair prognostic model predicting clinical events. Methods: We designed a prospective observational French multicentre study including 160 patients with significant functional TR (effective regurgitant orifice area >30mm 2 ) and LVEF >40%. Clinical, echocardiographic, and ECG data were collected at baseline, and at the 1- and 2-year follow-up. The primary outcome was all-cause death or hospitalization for heart failure. Results: At 2 years, 56 patients (35%) achieved the primary outcome. The subset with events showed more advanced right heart remodelling at baseline, but similar TR severity. Right atrial volume index (RAVI) and the TAPSE/sPAP ratio, reflecting right-ventricle-pulmonary artery coupling, were 73 mL/m 2 and 0.40 versus 64.7 mL/m 2 and 0.50 in the event vs event-free group, respectively (both p<0.05). None among all the clinical and imaging parameters tested had a significant group × time interaction. In multivariable analysis, the model including TAPSE/sPAP ratio >0.4 (OR=0.41, 95%CL 0.2 to 0.82) and RAVI >60 mL/m 2 (OR=2.13, 95%CL 0.96 to 4.75) permitted the fairest and most parsimonious prognostic evaluation. Conclusion: RAVI and TAPSE/sPAP are relevant for predicting the risk for event at 2-year follow-up in patient with an isolated functional TR. Funding Acknowledgement: Type of funding sources: None.